Letter (copy) : Assistance for Spain - Citrine, Walter, 1887-1983
030-0095-001 Secretary's. WMC/FC/EK/1576. FAS/JSS 9th August, 1938. Mr. F. A. Smith, Amalgamated Engineering Union, 110, Peckham Road, London, S.E.15. Dear Mr. Smith, ASSISTANCE FOR SPAIN. Many thanks for your letter of the 8th instant, from which I understand that you will again communicate with me in regard to the utilisation of the services of the International Solidarity Fund when the fund which you are raising reaches a substantial amount. Yours sincerely, General Secretary. 292/946/30/95